Selected Problems of Reinforced Soil Mechanics - Marek Kopinski; Andrzej Surowiecki (Communications - Scientific letters of the University of Zilina, 2002)
Selected problems of the mechanics of a loose soil medium, illustrated with tests of cuboidal specimens loaded with a vertical, static, axial symmetric pressure, have been presented. The specimens were reinforced with inserts (nets) situated horizontally, i.e. perpendicular to the plane of loading. The interaction between reinforced soil components, in particular the influence of soil and reinforcement related factors on the size of an interaction zone, was discussed.An average horizontal stress and an experimental coefficient of lateral pressure were taken into account when assessing the effect of reinforcement on the deformability of soil.